Early Buddhist oral tradition: textual formation and transmission - Anālayo (Wisdom Publications, 2022)
Introduction -- 1. The Recital of the Monastic Rules -- 2. Discourse and Verse Collections -- 3. Memory Errors -- 4. Systematization -- 5. Additions and Innovations -- 6. Implications of Orality -- Conclusion -- Abbreviations -- Notes -- References -- Index -- About the Author.